2021
DOI: 10.3390/su13105403
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Carbon Trading Scheme on Carbon Dioxide and Atmospheric Pollutants

Abstract: To estimate the synergistic emission reduction effect resulting from carbon emissions trading scheme (ETS) pilots launched in 2013, this study estimated the synergistic emission reduction relationship between carbon dioxide (CO2) and atmospheric pollutants, consisting of sulfur dioxide (SO2), nitrogen oxides (NOX), dust pollutants (Dust) and particulate matter 2.5 (PM2.5). Using the extended logarithmic mean Divisia index (LMDI) method and the IPAT equation, the synergistic emission reduction effect was decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 32 publications
3
18
0
Order By: Relevance
“…However, the study sample is divided in two types, one with tourism development on the left side of the axis of symmetry of the inverse U-shape and the other with tourism development on the right side. Our findings are consistent with Sun (2016a), (Feng et al 2021;Li et al 2021aLi et al , 2021c that concludes tourism has a positive impact on carbon dioxide emissions. Similarly, our results also show the negative impact of tourism on CO 2 emissions, which is consistent with the second category of literature (Katircioǧlu, 2014;Lee and Brahmasrene, 2013;Paramati et al, 2017).…”
Section: Analysis Of Gns Modelsupporting
confidence: 92%
“…However, the study sample is divided in two types, one with tourism development on the left side of the axis of symmetry of the inverse U-shape and the other with tourism development on the right side. Our findings are consistent with Sun (2016a), (Feng et al 2021;Li et al 2021aLi et al , 2021c that concludes tourism has a positive impact on carbon dioxide emissions. Similarly, our results also show the negative impact of tourism on CO 2 emissions, which is consistent with the second category of literature (Katircioǧlu, 2014;Lee and Brahmasrene, 2013;Paramati et al, 2017).…”
Section: Analysis Of Gns Modelsupporting
confidence: 92%
“…The model also combines green finance, ecological benefits, and financial development into one model and draws conclusions that are currently absent from the literature. In contrast to previous studies (Ali et al 2021 ; Cui et al 2020 ; Falcone 2020 ; Li et al 2021 ; Nawaz et al 2021 ), this one considers and compares the BRICS nations.…”
Section: Introductionmentioning
confidence: 96%
“…The researchers of the current period suggest that South Asia’s developing economies have three economic effects related to rising oil prices. [ 32 ] highlighted the increasing oil import costs, petroleum-related products’ short-term (flexibility in demand price) is shallow. Secondly, [ 33 ] suggested that international oil prices have not risen for domestic oil consumers, which has pushed up inflation.…”
Section: Introductionmentioning
confidence: 99%